Effect of extrusion conditions on the physical properties of coconut rice-based extrudates - K Dumchaiyapoom; P Hannanta-anan; M Phongpipatpong (My University, 2019)
Abstract Coconut meal is a by-product of coconut oil and coconut milk production. It is a rich source of dietary fiber which shows to have an important role in lowing the risk of various chronic diseases. Therefore, it is interesting to convert the coconut meal, previously recognized as a valueless by-product, into a nutritious food product. The aim of this work is to investigate the possibility of such conversion using a widely known extrusion method. The effect of extrusion variables, including the coconut meal content (0, 6, and 12 %), glutinous rice content (5, 10 and 15%) and screw speed of extruder (380, 400 and 420 rpm) were investigated on the properties of extruded products. Physical properties of the extrudates such as expansion ratio, density, water absorption index (WAI), water solubility index (WSI), crispness and moisture content were evaluated. Our study showed that the extrudates had expansion ratio of 2.30-2.78%, density of 0.55-0.76 g/cm 3 , WAI of 4.24-5.50 g/g, WSI of 21.51-33.37%, crispness of 16.87-27.73 kg.sec and moisture content of 6.76-8.27%. The regression models for true density, expansion ratio, crispness, WAI and WSI were derived and statistically significant ( p <0.05).
Keywords: Expansion ratio; Coconut oil; Food composition and properties